Optimasi Produksi Gula Merah Home Industry dari Nira Sawit dengan Model De Novo Programming - Windi Antika; Sajaratud Dur; Rima Aprilia (Universitas Islam Raden Rahmat, Malang, 2023)
The production optimization foreseen as a product of this research considers allfactors underlying the manufacturing process as well as the actual sales process,the use of well-realized materials that are not wasted, production costs that arewithin objectives or are minimum, and increased profits. maximum, resultingin increased productivity at its optimum. .The results of this analysiscontributed to the maximum suited production systems, allow companies tomore effectively serve their current market segments while managing productioncosts within a certain range, specifically from January to August 2022.Rp.361.783.536, Rp.314.659.450,-,Rp.359.995.170,-, Rp.463.712.680,-, Rp.363.159.610, Rp.337.190.940,-,Rp.342.852.270,-, Rp.355.165.890,- Themonthly increase in optimal profit by using the De Novo Programmingmethodology is equal to Rp.30.924.591,-, Rp.26.950.048,-, Rp.29.980.740,-,Rp.38.452.012,- Rp.30.549.026,-, Rp.28.322.755,-, Rp.28.913.288,- Rp.29.967.702,-